METHODICAL APPROACHES TO EVALUATION OF EFFICIENCY OF STATE REGULATION OF AGRICULTURAL SECTOR - NESENENKO, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern reforming of the economy is aimed at its balance and stability, as well as the need to ensure vital interests of society, dynamism of socio-economic development. Solving complex economic problems requires the formation and application of an institutional approach. The changes taking place in the modern economic system have a multifaceted nature, therefore the institutional support of the agrarian sphere as a part of the national economy must correspond to modern realities.Proper socio-economic development of the state depends on the general organization of state regulation, the separation of powers between authorities, and in the context of the development of the agrarian sector - on the assessment of the effectiveness of the executive power.The article analyzes the methodological apparatus for assessing the effectiveness of state regulation of the agrarian sector of the economy. Taking into account the goal, the main task of the study is to determine the criteria for evaluating the effectiveness of state regulation in the agricultural sector. On the basis of a critical analysis, groups of techniques for assessing the effectiveness of state support are singled out. An analysis of the methodological apparatus for assessing the effectiveness of state regulation of the agrarian sector of the economy was carried out. The criteria for evaluating the effectiveness of state regulation in the agricultural sector have been determined. The proposed methodology for assessing the effectiveness of state regulation of the agrarian sector of the economy, which should be aimed, first of all, at assessing the degree of solving the main problems that hinder the development of the industry, and assessing the level of influence of state support measures.
Keywords: state regulation; economic policy; agricultural sector; economic development